Langerhans cell histiocytosis with lung involvement in isolation and multisystem disease: Staging, natural history, and comparative survival. Issue 12 (8th October 2021) - Hazim, Antonious Z.; Ruan, Gordon J.; Hu, Marie; Ravindran, Aishwarya; Rech, Karen L.; Young, Jason R.; Cox, Christian W.; Abeykoon, Jithma P.; Scheckel, Caleb; Vassallo, Robert; Ryu, Jay H.; Tobin, W. Oliver; et al.
Abstract: Langerhans cell histiocytosis (LCH) is a histiocytic neoplasm that can involve the lungs as single system (LCH‐SSL) or multisystem disease (LCH‐MSL). The role of full‐body radiographic staging to determine whether patients have LCH‐SSL or LCH‐MSL is unclear. Long‐term outcomes of LCH‐SSL versus LCH‐MSL and multisystem without lung involvement (LCH‐MSNL) are unknown. A retrospective study of adult LCH patients seen at our center from January 2000 to 2020 was performed. In Part 1, we addressed utility of whole‐body staging imaging among those presenting with isolated pulmonary signs or symptoms. Staging was defined as fluorodeoxyglucose positron emission tomography‐computed tomography (CT) or whole‐body CT obtained within 3 months of diagnosis. In Part 2, we examined the frequency of developing extra‐pulmonary disease over time and mortality in patients with LCH‐SSL. In Part 3, we compared the overall survival of LCH‐SSL, LCH‐MSL, and LCH‐MSNL. Part 1: 240 patients with LCH were identified. A total of 112 (47%) had pulmonary signs or symptoms at presentation. Thirty‐four (30%) underwent radiographic staging and only one showed evidence of extra‐pulmonary disease. Part 2: 108 (45%) were LCH‐SSL. Median follow‐up duration of 4.5 years (95% confidence interval [CI]: 2.9–6.0). None developed extra‐pulmonary disease. Part 3: 5‐year survival: 94% (95% CI: 84%–98%) for LCH‐SSL, 78% (95% CI: 59%–90%) for LCH‐MSL, and 75% (95% CI: 53%–89%) for LCH‐MSNL. LCH patients presenting with isolated pulmonary signs or symptoms rarely have extra‐pulmonary involvement at the time of diagnosis and generally do not develop extra‐pulmonary progression. LCH‐SSL has the best overall survival, while LCH‐MSL and LCH‐MSNL have similar clinical outcomes.